Surgical repair of a giant coronary artery aneurysm. Issue 9 (28th May 2021) - Soletti, Giovanni Jr; Lau, Christopher; Cancelli, Gianmarco; Robinson, N. Bryce; Audisio, Katia; Girardi, Leonard N.; Gaudino, Mario
Abstract: We present a rare case of a giant coronary aneurysm of the circumflex artery measuring 4.8 × 4.2 × 7.2 cm in a 67‐year‐old man, recently diagnosed with type B aortic dissection. Surgical management was successfully performed by proximal end ligation and bypass of the dual‐ostium distal end with a reverse saphenous vein graft.